Koping Positif Warga Binaan Pemasyarakatan dalam Menghadapi Stigma dan Diskriminasi - Nitsae, Veronika; Andriany, Megah; Mu’in, Muhammad (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Stigma and discrimination are more common among women and affect the development of coping skills for women with HIV. Research related to coping strategies for prisoners with HIV in prisons is still very limited. This study aimed to identify the positive coping methods used and the reasons for using these coping strategies in dealing with stigma and discrimination against female inmates with HIV.Methods: This research method is a qualitative descriptive phenomenological design. The population of this study was female inmates living with HIV with a total of eight participants. Sampling was done by purposive sampling technique. Data was collected through in-depth interviews and analyzed using the Colaizzi technique.Results: The results of the study found two themes: (1) don't care and stay away from people who cause stigma to avoid problems; (2) attract sympathy and be honest with others to lighten the burden on the mind.Conclusion: Indifference certainly does not always have positive but also negative implications such as the emergence of disputes or divisions and individualism among prisoners. Meanwhile, active coping such as telling the truth can improve prisoners' physical and psychological well-being. The development of intervention programs such as narrative enhancement and cognitive therapy (NECT), family therapy, spiritual emotional freedom technique (SELF), and HIV peer support groups in prisons to develop active coping for female inmates with HIV in facing internal and public stigma is urgently needed. Keywords: Coping, Correctional Setting, Discrimination Stigma, HIV.